FRI0572 Social and Emotional Impact of Rheumatic Diseases in Patients Treated with Subcutaneous Biological Therapy. Rheu Life Survey. (15th July 2016) - Batlle, E.; González, C.M.; Carmona, L.; Torralba Gόmez-Portillo, A.I.; Cea-Calvo, L.; Arteaga, M.J.; de Toro, F.J.
Abstract : Background: Rheumatic diseases impair patients' everyday life but this is rarely assessed in clinical studies. Objectives: To describe the social and emotional impact perceived, as a consequence of the disease, by patients with rheumatoid arthritis (RA), axial spondyloarthritis (SpA) and psoriatic arthritis (PsA) treated with biological drugs. Methods: RHEU-LIFE was a survey to patients with RA, axial SpA and PsA from Spain. Rheumatologists from 50 outpatient hospital clinics handed the survey to 20 consecutive patients >18 years-old who attended the clinic, they completed the survey at home and returned by pre-paid post mail. Patients were surveyed on the perceived impact of their rheumatic disease on five areas: 1) quality of life in general; 2) emotional state; 3) work or daily activity; 4) personal relations and 5) life of their families, responding with the options "no impact", "some", "moderate" or "severe". Results: The survey was given to 1000 patients; 592 responded (response rate 59.2%, mean age 51.7 years [SD 13.2], 42.4% men and 57.6% women). Patients' disease were RA (n=304, 54.2%), axial SpA (n=141, 25.1%) and PsA (n=116, 20.7%). 31 patients did not identify their disease. The percentage of patients who considered that the disease moderately or severely affected the different areas is shown in the table. A higher percentage of women vs men declared that the disease moderately or greatly affected all the areas (table). Similarly, aged patients described a greater impact than those who were younger (table). No differences were observed with regard to the disease, with similar percentages of patients with RA, axial SpA or PSA declaring "moderate" or "severe" impact in all areas (all, p>0.1). Conclusions: Patients with RA, axial SpA and PsA treated with biological drugs describe a significant impact in their quality of life, work or daily activity, emotional state, personal relations and life of their families, especially women and elderly patients. The impact was ranked similarly regarding the baseline disease. Acknowledgement: This survey was financed by Merck Sharp & Dohme of Spain and endorsed by the patients' association ConArtritis (Arthritis National Coordinator). Disclosure of Interest: None declared